Wspieranie innowacyjności sektora MŚP - Braziewicz-Kumor, Olga (SME Sector Innovation Support, 2008)
In the recent years there can be observed an increasing interest in the innovation policy and its influence on the economic growth of the European Union, particular countries or even regions. It is not the purpose of this article to define innovation and the impact on competitiveness - these issues have been broadly discussed in numerous academic publications. Some crucial questions still remain: why the results of innovation in Polish conditions diverge from the results in other developed countries and what the barriers preventing companies from innovation implementation are. And above all, is the method of innovation support system in Poland efficient in surmounting the existing barriers? (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 126-135